2016
DOI: 10.1007/s00371-016-1239-7
|View full text |Cite
|
Sign up to set email alerts
|

A study on user preference of high dynamic range over low dynamic range video

Abstract: The increased interest in high dynamic range (HDR) video over existing low dynamic range (LDR) video during the past decade or so was primarily due to its inherent capability to capture, store and display the full range of real-world lighting visible to the human eye with increased precision. This has led to an inherent assumption that HDR video would be preferable by the end-user over LDR video due to the more immersive and realistic visual experience provided by HDR. This assumption has led to a considerable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Akyüz et al [23] demonstrated that participants prefer a HDR image over tone-mapped or LDR image of a scene, Mukherjee et al [24] showed that this also holds true for HDR video. Melo et al [25] investigated tone-mapped HDR content on an LDR display to find that the ambient illumination, and especially reflections on the screen, significantly affected the viewing experience.…”
Section: Subjective Evaluationmentioning
confidence: 99%
“…Akyüz et al [23] demonstrated that participants prefer a HDR image over tone-mapped or LDR image of a scene, Mukherjee et al [24] showed that this also holds true for HDR video. Melo et al [25] investigated tone-mapped HDR content on an LDR display to find that the ambient illumination, and especially reflections on the screen, significantly affected the viewing experience.…”
Section: Subjective Evaluationmentioning
confidence: 99%
“…However, other studies have evaluated more specific variables such as the overall similarity, the similarity in bright and dark areas, and the color fidelity [2,4]. A more recent study was conducted to test the veracity of the assumption that HDR video would be preferable by the end-user over SDR video [34].…”
Section: Subjective Evaluation Of Inverse Tone Mapping Techniquesmentioning
confidence: 99%
“…High‐dynamic‐range (HDR) content is now being produced that exercises large contrast within an image and dramatic temporal changes in which different scenes can have very different peak brightness . High brightness and deep contrast are widely accepted as being the key contributors to the dramatic improvements in visual quality associated with the emerging ultra‐high‐definition image format . The content in this new format has largely outpaced the ability of conventional display systems to fully render the extended dynamic range.…”
Section: Objective and Backgroundmentioning
confidence: 99%
“…1 High brightness and deep contrast are widely accepted as being the key contributors to the dramatic improvements in visual quality associated with the emerging ultra-high-definition image format. 2,3 The content in this new format has largely outpaced the ability of conventional display systems to fully render the extended dynamic range. Several technological approaches have emerged to extend the dynamic range of liquid crystal (LC) display systems.…”
Section: Objective and Backgroundmentioning
confidence: 99%